Odpowiedzi

2010-02-25T19:25:19+01:00
3m+n=9
2m-5n=-11

n=9-3m
2m-5n=-11

2m-5(9-3m)=-11
2m-45+15m=-11
17m=-11+45
17m=34 /:17
m=2

n=9-3*2
n=9-6
n=3

m=2
n=3
1 5 1
2010-02-25T19:26:58+01:00
3m+n=9 /*5
2m-5n=-11

15m+5n=45
2m-5n=-11 5n i -5n sie skraca

15m=45
2m=-11 dodajemy góra dół

17m=34/:2
m=2 m podstawiamy do dowolnego rówania


3*2+n=9
6+n=9
n=3 m=2 n=3




2010-02-25T19:28:12+01:00
{3m+n=9
2m-5n=-11

n=9-3m
2m-5(9-3m) = -11

n=9-3m
2m-45+15m= -11

n=9-3m
17m= -11+45

n=9-3m
17m=34

n=9-3m
m=34:17

n=9-3m
m=2

n=9-3*2=9-6=3

m=2
n=3
Spr
L=3m+n= 3*2+3=6+3=9
L=P
L=2m-5n= 2*2-5*3=4-15= -11
L=P